- Musik Mozart Memiliki Ekspresi Brain Deriverd Neurotrophic Factor Tertinggi Pada Serebrum dan Serebellum Rattus norvegicus Dibandingkan Dengan Gamelan Jawa, Sunda Dan Bali Selama Kehamilan - Virki Widoyanti; Hermanto Tri J; Widjiati Widjiati (Akademi Keperawatan Dharma Husada Kediri, 2020)
Introduction: Music can affect the parasympathetic nervous system or the automatic nervous system, both directly and indirectly. The exposure of Mozart's music, Javanese, Sundanese and Balinese gamelan influences neurotropic factors in the brain. Methods: This study was an experimental laboratory with a random post-test design only in the design of the control group used by Rattus norvegicus as a model. Results: There were significant differences in brain deriverd neurotrophic factor expressions in Rattus norvegicus children between groups with p = 0.018 (mean 1.60 ± 0.42 for the control group, 4.00 ± 1.85 for the mozart music group, 3.00 ± 0.96 for Javanese gamelan groups, 2.48 ± 0.68 Sundanese Gamelan groups, and 2.16 ± 1.27 in Balinese Gamelan groups) also in the cerebellum with p = 0.022 (average 1, 44 ± 0 , 29 for the control group, 3.92 ± 1.81 for the Mozart event, 3.04 ± 0.94 Javanese gamelan groups, 2.92 ± 0, 41 Sundanese gamelan groups, and 2.57 ± 1,053 Balinese gamelan groups). Discussion: There are differences in the expression of brain derived neurotrophic factors in the cerebrum and Rattus norvegicus cerebellum between those exposed to Mozart music, Javanese, Sundanese, Balinese gamelan and control.. Key words : Mozart, Javanese Gamelan, Sundanese Gamelan, Balinese Gamelan, Brain Deriverd Neurotrophic Factor